Social Identity and Ethnicity in Electoral Democracy: an Islamic Moderation Perspective from South Sumatra's Muslim Community - Faisal Amrullah; Rina Antasari; Holijah Holijah; Mohammaf Syawaludin; Mohammad Toriq (MUSLIM HERITAGE, 2026)
Abstract This study examines the role of social identity and ethnicity in shaping electoral democratic practices within Muslim societies, positioning Islamic moderation as a socio religious perspective that explains how the values of justice, balance (wasathiyah), and social cohesion limit the politicization of identity in political contests. The primary issue examined is how the mobilization of ethnicity-based social identity influences the quality of democracy and social cohesion. The objective of this study is to analyze the implications of social identity and ethnicity on electoral democracy within the framework of Islamic moderation. This study employs an empirical qualitative approach through in depth interviews with community leaders, religious figures, and Muslim voters, as well as field observations in the ethnically diverse region of South Sumatra, and analysis of documents related to general elections. Research subjects were selected through purposive sampling based on their active involvement in socio-political dynamics and experience in the electoral process. The findings indicate that social identity and ethnicity play a dual role in electoral democracy: they both encourage political participation and have the potential to trigger social polarization. This study found that Islamic moderation functions not only as a normative value but also as a social mechanism that actively limits the politicization of ethnic identity and restores social cohesion post-election, thereby making a significant contribution to strengthening the study of Islamic social dynamics within the context of electoral democracy.   Abstrak Studi ini meneliti peran identitas sosial dan etnisitas dalam membentuk praktik demokrasi elektoral di masyarakat Muslim, dengan menempatkan moderasi Islam sebagai perspektif sosial-religius yang menjelaskan bagaimana nilai-nilai keadilan, keseimbangan (wasathiyah), dan kohesi sosial membatasi politisasi identitas dalam kontes politik. Isu utama yang diteliti adalah bagaimana mobilisasi identitas sosial berbasis etnisitas memengaruhi kualitas demokrasi dan kohesi sosial. Tujuan studi ini adalah untuk menganalisis implikasi identitas sosial dan etnisitas terhadap demokrasi elektoral dalam kerangka moderasi Islam. Studi ini menggunakan pendekatan kualitatif empiris melalui wawancara mendalam dengan para pemimpin masyarakat, tokoh agama, dan pemilih Muslim, serta observasi lapangan di wilayah Sumatera Selatan yang beragam etnis, dan analisis dokumen terkait pemilihan umum. Subjek penelitian dipilih melalui pengambilan sampel bertujuan berdasarkan keterlibatan aktif mereka dalam dinamika sosial-politik dan pengalaman dalam proses pemilihan. Temuan menunjukkan bahwa identitas sosial dan etnisitas memainkan peran ganda dalam demokrasi elektoral: keduanya mendorong partisipasi politik dan berpotensi memicu polarisasi sosial. Studi ini menemukan bahwa moderasi Islam tidak hanya berfungsi sebagai nilai normatif tetapi juga sebagai mekanisme sosial yang secara aktif membatasi politisasi identitas etnis dan memulihkan kohesi sosial pasca pemilu, sehingga memberikan kontribusi signifikan untuk memperkuat studi dinamika sosial Islam dalam konteks demokrasi elektoral.